Vacuolar targeting of recombinant antibodies in Nicotiana benthamiana. Issue 12 (14th June 2016) - Ocampo, Carolina Gabriela; Lareu, Jorge Fabricio; Marin Viegas, Vanesa Soledad; Mangano, Silvina; Loos, Andreas; Steinkellner, Herta; Petruccelli, Silvana
Summary: Plant‐based platforms are extensively used for the expression of recombinant proteins, including monoclonal antibodies. However, to harness the approach effectively and leverage it to its full potential, a better understanding of intracellular processes that affect protein properties is required. In this work, we examined vacuolar (vac) targeting and deposition of the monoclonal antibody (Ab) 14D9 in Nicotiana benthamiana leaves. Two distinct vacuolar targeting signals (KISIA and NIFRGF) were C‐terminal fused to the heavy chain of 14D9 (vac‐Abs) and compared with secreted and ER‐retained variants (sec‐Ab, ER‐Ab, respectively). Accumulation of ER‐ and vac‐Abs was 10‐ to 15‐fold higher than sec‐Ab. N‐glycan profiling revealed the predominant presence of plant typical complex fucosylated and xylosylated GnGnXF structures on sec‐Ab while vac‐Abs carried mainly oligomannosidic (Man 7‐9) next to GnGnXF forms. Paucimannosidic glycans (commonly assigned as typical vacuolar) were not detected. Confocal microscopy analysis using RFP fusions showed that sec‐Ab‐RFP localized in the apoplast while vac‐Abs‐RFP were exclusively detected in the central vacuole. The data suggest that vac‐Abs reached the vacuole by two different pathways: direct transport from the ER bypassing the Golgi (Ab molecules containing Man structures) and trafficking through the Golgi (for Ab molecules containing complex N‐glycans). Importantly, vac‐Abs were correctly assembled and functionally active. Collectively, we show that the central vacuole is an appropriate compartment for the efficient production of Abs with appropriate post‐translational modifications, but also point to a reconsideration of current concepts in plant glycan processing.